Notation and transcription for the berimbau employed in capoeira (2007)
This paper discusses the importance of musical notationand transcription systems for the Brazilian berimbauwithin the context of Capoeira, a musical tradition towhich it is profoundly bound but that is undeniablybeing influenced by new media. In order to analyzeexisting notation and transcription systems, this paperproposes categories of creators or users of such systemsalong a continuum of Capoeira insiders and amp; outsiders. Itplaces special emphasis on the role of the outsider inthe creation and use of these methods depending onhis/her immersion in Capoeira and his/her training inother written musical traditions.